2022
DOI: 10.1111/aos.15145
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of reticular pseudodrusen in the Russian Ural Eye and Medical Study

Abstract: Purpose: To assess the prevalence of reticular pseudodrusen (RPD) and their determinants. Methods: The Population-based Ural Eye and Medical Study conducted in Bashkortostan/Russia included 5899 participants aged 40+ years. Presence of RPDs was assessed on conventional colour fundus photographs, red-free fundus images and optical coherence tomographic images. Results:The study included 4914 (83.3%) individuals (mean age: 58.5 AE 10.5 years; range: 40-94 years). Using two age limits (>55 years and 40+ years) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Our study confirms the previously reported association of SDD with age [ 13 , 15 ], and we found that only two relatives with SDD had AMD-defining retinal lesions such as intermediate/large drusen or pigmentary abnormalities but showed small alterations such as druplets. This may indicate an independency of SDD from AMD (particularly in the early course of disease) and/or suggest that SDD could be a precursor in those at risk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirms the previously reported association of SDD with age [ 13 , 15 ], and we found that only two relatives with SDD had AMD-defining retinal lesions such as intermediate/large drusen or pigmentary abnormalities but showed small alterations such as druplets. This may indicate an independency of SDD from AMD (particularly in the early course of disease) and/or suggest that SDD could be a precursor in those at risk.…”
Section: Discussionsupporting
confidence: 93%
“…All these findings point at different underlying disease pathways in presence of SDD prior leading towards outer retinal atrophy compared to eyes without SDD [ 10 ]. However, overall prevalence estimates vary significantly from 0.41 to 18.1% between studies depending on imaging modalities [ 11 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As also described in detail previously, all study participants underwent a detailed interview which was conducted by trained social workers and consisted of more than 250 standardized questions on the socio-economic background and lifestyle parameters, depression and anxiety, and known diagnosis and therapy of major diseases 23,24,[26][27][28] . The series of examinations included anthropometry, blood pressure measurement, handgrip dynamometry, spirometry, biochemical analysis of blood samples taken under fasting conditions, and ophthalmologic examinations.…”
Section: Examinationsmentioning
confidence: 99%